2018
DOI: 10.1007/s12035-018-1062-4
|View full text |Cite
|
Sign up to set email alerts
|

Tauroursodeoxycholic Acid Improves Motor Symptoms in a Mouse Model of Parkinson’s Disease

Abstract: Parkinson's disease (PD) is characterized by severe motor symptoms, and currently there is no treatment that retards disease progression or reverses damage prior to the time of clinical diagnosis. Tauroursodeoxycholic acid (TUDCA) is neuroprotective in the 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP) mouse model of PD; however, its effect in PD motor symptoms has never been addressed. In the present work, an extensive behavior analysis was performed to better characterize the MPTP model of PD and to eva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
51
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 72 publications
(57 citation statements)
references
References 64 publications
6
51
0
Order By: Relevance
“…In humans, defective protein folding is thought to be connected with many neurodegenerative diseases [12,122]. In this respect, TUDCA not only has been shown to inhibit apoptosis induced by several stimuli in neuronal cells in vitro, but also to play a cytoprotective role in animal models of neurological disorders, such as Alzheimer's disease (AD) [6,35,[123][124][125], Parkinson's disease (PD) [3,6,[126][127][128][129][130], Huntington's disease (HD) [24,131], amyloid latheral sclerosis (ALS) [132][133][134], and Prion diseases [135]. Furthermore, pretreatment with TUDCA significantly reduced glutamate-induced apoptosis of rat cortical neurons [38] and improved synaptic plasticity as well as cognitive and motor impairment in the hippocampus of microcystin-leucine-arginine-treated rats [136,137].…”
Section: Tudca In Neurodegenerative Diseasesmentioning
confidence: 99%
See 2 more Smart Citations
“…In humans, defective protein folding is thought to be connected with many neurodegenerative diseases [12,122]. In this respect, TUDCA not only has been shown to inhibit apoptosis induced by several stimuli in neuronal cells in vitro, but also to play a cytoprotective role in animal models of neurological disorders, such as Alzheimer's disease (AD) [6,35,[123][124][125], Parkinson's disease (PD) [3,6,[126][127][128][129][130], Huntington's disease (HD) [24,131], amyloid latheral sclerosis (ALS) [132][133][134], and Prion diseases [135]. Furthermore, pretreatment with TUDCA significantly reduced glutamate-induced apoptosis of rat cortical neurons [38] and improved synaptic plasticity as well as cognitive and motor impairment in the hippocampus of microcystin-leucine-arginine-treated rats [136,137].…”
Section: Tudca In Neurodegenerative Diseasesmentioning
confidence: 99%
“…The second most common neurodegenerative disorder worldwide is Parkinson's disease [127]. PD is characterized by the loss of dopaminergic neurons in the substantia nigra of the brain, which results in severe motor symptoms such as dyskinesia, tremor, and speech impairment [3,[127][128][129][130]. Dopamine cell death in PD may result from either genetic or environmental factors.…”
Section: Tudca In Neurodegenerative Diseasesmentioning
confidence: 99%
See 1 more Smart Citation
“…A phase 1, open-label trial evaluating the safety and pharmacokinetics of 50mg/kg/day UDCA in 20 patients with PD is currently underway (NCT02967250) while a trial of UDCA in PD patients to evaluate the effect of on disease progression has received funding and is due to start imminently. PD-specific pharmacokinetic data regarding UDCA is awaited though in view of the potential issues regarding incomplete absorption of UDCA from the gut, interest is growing in the UDCA derivative tauro-ursodeoxycholic acid (TUDCA) (not currently approved for use), which has demonstrated better orally bioavailability, crosses the blood-brain barrier and has demonstrated neuroprotection against MPTP-and α-synuclein-induced stress in vitro and in vivo [72,[77][78][79] and indicated potential benefits in a small RCT in 34 patients with ALS [80] and may offer better potential.…”
Section: Ursodeoxycholic Acid (Udca)mentioning
confidence: 99%
“…Recently, Rosa A, et al have shown in mice that some BAs, in particular tauroursodeoxycholic acid, act as mitochondrial sta-bilizer and anti-apoptotic agent in a number of models of neurodegenerative diseases, including PD. This substance prevented a decrease of dopaminergic fibers and ATP levels, mitochondrial dysfunction and neuroinflammation [23].…”
Section: Resultsmentioning
confidence: 95%